COMPARATIVE EVALUATION OF THE POLYMER DISPERSIONS FOR THE FIBROUS MATERIALS SURFACE FUNCTIONALIZATION - ПЛАВАН, В. П.; КОЛОДІЙ, А. І.; ОХМАТ, О. А.; БОЙЧЕНКО, А. Ю.; ЛАТИШЕВ, Д. О. (Technologies and Engineering, 2024)
Purpose. The purpose of the work is to analyze the properties of polymer dispersions with different chemical composition to determine the possibility of their further use as part of polymer coatings for the functionalization of fibrous materials. Methodology. Different types of polymer materials have used in the work: Plextol UltraFine PR 3500K (Synthomer, Germany), Vinavil Eva 1612 (Vinavil, Italy), Crilat 4815 (Vinavil, Italy), Impranil DLP-R (Covestro, Germany). The quality of water-emulsion film-forming systems and the possibility of their use in the process of functionalization of the surface for fibrous bases have determined by the content of dry residue and viscosity, pH, film-forming ability and resistance to the action of electrolytes. Findings. A comparative assessment of water-dispersible acrylic, vinyl and urethane polymers have made in order to determine the possibility of their further application for the functionalization of the surface of fibrous bases. It was determined that all polymer dispersions show resistance to the action of ammonium hydroxide. In addition, all polymer dispersions (with the exception of the aqueous dispersion of acrylic copolymer Plextol UltraFine PR 3500K) are resistant to sodium chloride, ammonium sulfate, and acetic acid. Given the close pH value, almost all polymer dispersions can be mixed without the risk of coagulation. In the future, it is of interest to determine the possibility of combining Crilat 4815 and Impranil DLP-R polymer dispersions when creating a hybrid acrylic-urethane coating for fibrous bases, given their similar resistance to electrolytes. Originality. Finely dispersed emulsions of film-forming acrylic-urethane polymers of the new generation are able to modify the surface of the fibrous material through interaction with its functional groups, which makes it possible to create competitive fabrics with improved stable properties, in particular for technical applications. Practical value. New types of water-dispersion systems on acrylic and urethane polymers are proposed for modifying the surface of fabrics in order to give fabrics new functional properties. It is expected that in these hybrid dispersions, the acrylic component will provide resistance to the action of alkalis and to external influences, while the polyurethane will increase the strength, flexibility and homogeneity of the formed film.